PENGARUH DIGITAL MARKETING DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA COFFE SHOP CAPTAIN CO - Azmi, Sarah (JURNAL LENTERA BISNIS, 2026)
The increasingly sophisticated era of globalization has made it easier for people to access information, creating a modern mindset and changing lifestyles that drive people to do business, especially coffee shops. However, doing business is not just about selling, but also requires a strong strategy in an era of fierce competition. The purpose of this study is to examine the influence of digital marketing and service quality on purchasing decisions at Captain Co Coffee Shop. This study uses primary data obtained by distributing questionnaires to the selected population, namely visitors to Captain Co Coffee Shop, with a sample of 70 respondents using the Malhotra formula. The results of this study on the influence of digital marketing and service quality on purchasing decisions at Captain Co. Coffee Shop are positive. Therefore, it can be concluded that digital marketing influences purchasing decisions at Captain Co. Coffee Shop, service quality influences purchasing decisions, and digital marketing and service quality simultaneously influence purchasing decisions at Captain Co. Coffee Shop.